Islamic perspectives on environmental and waste management issues - Muyibi, Suleyman Aremu; Jamal, Parveen; Mohd. Salleh, Hamzah (Serials Publications, 2005)
In this paper, Islamic approaches to environmental and waste management issues are explored. Environmental philosophy based on the Qur'an and Prophetic Traditions (Sunnah) is that there is a fundamental link and interdependency between all natural elements which is based on the premise that if man abuses or exhausts one element, the natural world as a whole will suffer direct consequences. The holistic principle of environmental management as applied by the Prophet Muhammad (s.a.w) is based on three important principles made up of the concepts of oneness of God (tauhid), stewardship (khalifah) and trust (amana). The Islamic approach to maintaining a balance between material development and responsibility will be explores as applied in waste management and pollution control. the detrimental effects of pollution will also be discussed and Islamic guidelines to ensure balance between material development and responsibility highlighted. the concept of wastes as a resource to be used to reduce pollution as well as efficient utilization of scarce natural resources through bioconversion, recycling, and reuse will also be stressed.